The gut microbiota modulates host amino acid and glutathione metabolism in mice. Issue 10 (16th October 2015) - Mardinoglu, Adil; Shoaie, Saeed; Bergentall, Mattias; Ghaffari, Pouyan; Zhang, Cheng; Larsson, Erik; Bäckhed, Fredrik; Nielsen, Jens
Abstract: The gut microbiota has been proposed as an environmental factor that promotes the progression of metabolic diseases. Here, we investigated how the gut microbiota modulates the global metabolic differences in duodenum, jejunum, ileum, colon, liver, and two white adipose tissue depots obtained from conventionally raised (CONV‐R) and germ‐free (GF) mice using gene expression data and tissue‐specific genome‐scale metabolic models (GEMs). We created a generic mouse metabolic reaction (MMR) GEM, reconstructed 28 tissue‐specific GEMs based on proteomics data, and manually curated GEMs for small intestine, colon, liver, and adipose tissues. We used these functional models to determine the global metabolic differences between CONV‐R and GF mice. Based on gene expression data, we found that the gut microbiota affects the host amino acid (AA) metabolism, which leads to modifications in glutathione metabolism. To validate our predictions, we measured the level of AAs and N‐acetylated AAs in the hepatic portal vein of CONV‐R and GF mice. Finally, we simulated the metabolic differences between the small intestine of the CONV‐R and GF mice accounting for the content of the diet and relative gene expression differences. Our analyses revealed that the gut microbiota influences host amino acid and glutathione metabolism in mice. Synopsis: Tissue‐specific genome‐scale metabolic models (GEMs), transcriptomic and metabolomic analyses reveal global metabolic differences between conventionally raised and germ‐free mice and show that the gut microbiota affects host amino acid and glutathione metabolism. A generic Mouse Metabolic Reaction GEM (MMR) is created using the mouse orthologs of human genes in HMR2. Tissue‐specific GEMs for 28 mouse tissues are reconstructed and applied for the analysis of global gene expression data. Microbial‐induced metabolic differences in the small intestine are simulated using the relative metabolic differences (RMetD) method. The model predictions are validated by measuring amino acid levels in the portal vein. Abstract : Tissue‐specific genome‐scale metabolic models (GEMs), transcriptomic and metabolomic analyses reveal global metabolic differences between conventionally raised and germ‐free mice and show that the gut microbiota affects host amino acid and glutathione metabolism.